2018
DOI: 10.1016/j.heliyon.2018.e00881
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pennyroyal, savory and thyme essential oils on Japanese quail physiology

Abstract: An experiment was conducted to show the effects of different levels of pennyroyal, thyme and savory essential oils dietary supplementation on performance, organs weight, intestinal morphology, and serum lipids in quails. A total of 550 day-old Japanese quail chicks were allocated into 11 dietary treatments of 5 replications (10 birds in each cage) under a randomized experimental design. The treatments were a basal diet (Control), or 3 levels (200, 300, and 400 ppm) of thyme essential oil (TO), or 3 levels (200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Such beneficial effects are mainly attributed to the carvacrol antioxidant as well as anti-inflammatory effects ( Alagawany et al., 2015 , Lahmar et al., 2018 , Forte et al., 2018 ). Moreover, essential oils, such as SkEO, have shown to assist in improved digestive processes ( Lee et al., 2004 ), increased absorption of some nutrients ( Dehghani et al., 2018 ), and consequently enhanced growth and productive performance via modification and activation of gastrointestinal tract structure and function and to inhibit/prevent gut disorders ( Alagawany et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such beneficial effects are mainly attributed to the carvacrol antioxidant as well as anti-inflammatory effects ( Alagawany et al., 2015 , Lahmar et al., 2018 , Forte et al., 2018 ). Moreover, essential oils, such as SkEO, have shown to assist in improved digestive processes ( Lee et al., 2004 ), increased absorption of some nutrients ( Dehghani et al., 2018 ), and consequently enhanced growth and productive performance via modification and activation of gastrointestinal tract structure and function and to inhibit/prevent gut disorders ( Alagawany et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, researchers have linked phenolic compounds, viz. simple phenolic, phenolic acids, anthocyanin, and flavonoids of several plants with the plants, antioxidant potentials, which include free radicals scavenging, and reducing power activity [45][46][47] . Earlier studies also reported phenolic compounds as reducing agents, hydrogen givers, singlet oxygen inhibitors, and effective metal chelators because of their redox properties 5,14 .…”
Section: Assaymentioning
confidence: 99%
“…However, excessive dosage of thyme essential oil can deteriorate gut integrity, as shown by studies on laying hens (Placha et al, 2010). By contrast, thyme and savory essential oils affect the height of villi in the duodenum, jejunum and ileum, and reduce the depth of crypts, as demonstrated by studies on Japanese quails (Dehghani et al, 2018). Studies involving pigs revealed that a mix of thyme and peppermint essential oils and a plant extract of oregano had a positive effect on the microbiological profile of the large intestine, which was manifested by a significant increase in the count of probiotic bacteria (Ruzauskas et al, 2020).…”
Section: Herbal Active Substancesmentioning
confidence: 99%